AKTIFITAS FISIK DAN PENGGUNAAN ENERGI PEKERJA LAKI-LAKI DENGAN JENIS PEKERJAAN BERBEDA - Rosmalina, Yuniar; Permaesih, Dewi (PERSATUAN AHLI GIZI INDONESIA, 2008)
PHISICAL ACTIVITY AND ENERGY EXPENDITURE OF MALE WORKER WITH DIFFERENT ACTIVITY LEVELDaily physical activities considered as main component in estimating energy expenditure for group ofcommunity. Data on physical activities of male worker relating to their job/occupation in Indonesian isstill rarely found. The objective of the study is to compare daily physical activities and daily energyexpenditure of male workers with different of their activity level.Respondents were 51 male workers considered as light activity level and 50 as heavy activity level.Data collection including anthropometric measurement, physical activities was measured at their joblocation using combination of observation method and recall method 5 day consecutively. Total energyexpenditure was estimated using factorial estimated of total energy expenditure. The results showedthat male worker with light activity level spent their time in doing their job significantly longer than highactivity level (589 minutes vs. 520 minutes). However in term of the energy cost for their doing the jobthe male worker with high activity level was higher compared to male worker with light activity level(2273 Kcal vs. 1242 Kcal). Mean value daily total energy expenditure was 2408 Kcal/day for lightactivity and 3548 Kcal/day for high activity.Keywords: physical activities, energy expenditure, male worker.